Employing public relations publications to achieve the goals of sports institutions - abdkader aathmaned, nacereddin; abdkader aathmaned, Mohammed (sports creativity, 2025)
The study aimed to identify ways to employ public relations in sports institutions, and to what extent public relations publications succeeded in achieving the required communication goal, this research is descriptive research in which the researchers used the survey studies approach, and the research community included workers in the field of sports media in the capital Khartoum , Where the research sample was chosen in a stratified, randomized manner with proportional distribution, and tools were used to collect information, which is the questionnaire and the scientific interview, and the study came out with a number of results, the most important of which are: 55% of the research community believes that public relations publications address rumors that hit sports institutions. 45% of the research community believes that public relations publications did not contribute to reflecting the view of sports organizations. And if the same research community, with 71%, is interested in public relations publications issued by sports organizations. 50% believe that sports organizations do not realize the importance of public relations publications, and that 43% believe that the publications of sports institutions have not succeeded in providing the media with sufficient information